How Does the Optimism of Students Learning a Foreign Language Affect Their Creative Self-Efficacy? The Mediating Effects of Hope and Empathy - Lei, Fei; Lei, Lin (Frontiers in Psychology, 2022)
Creative self-efficacy (CSE) is a core influencer of creative behavior and has a positive impact on well-being and development. However, the positive psychological processes that help to promote CSE in foreign-language learning (FLL) remain under-studied. Focusing specifically on FLL students, the present study examined the associations among optimism, hope, empathy, and CSE and investigated the possible mediating roles of hope and empathy in the relationship between optimism and CSE. A sample of 330 FLL students from two Chinese universities participated in this study. The results showed that (i) optimism, hope, and empathy were all positively related to CSE and that (ii) optimism did not directly predict CSE but indirectly and positively predicted CSE through hope and empathy. These findings suggest that optimism, empathy, and hope potentially play positive roles in facilitating CSE in FLL students. Based on the present results, some practical approaches are discussed that could help improve the CSE of FLL students, paying particular attention to the effects that potentially motivate their positivity.